Cavernous hemangioma of the retina – case report - Pawlik, Beata; Figurska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Cavernous hemangioma of the retina is a rare, congenital, benign, typically unilateral retinal vascular tumor, occurring predominantly in children and young adults. The aim of this paper is to present the case of a 36-year-old patient with macular cavernous hemangioma of the retina complicated by hemorrhage and deterioration in visual acuity. Treatment involved intravitreal injections of the vascular endothelial growth factor (VEGF) inhibitor bevacizumab, used off-label, which resulted in both functional and morphological improvement. The case discussed highlights the importance of differential diagnosis of cavernous hemangioma of the retina with other vascular anomalies of the fundus as well as diagnostic evaluations including central nervous system or genetic examinations.